The region Collisuyo and ethnic groups - Espinoza Soriano, Waldemar (2015)
Southwest of the fourth region of the empire of the Incas, called Cuntisuso, and west of Collasuyu existed subregion have called Collisuyu. He understood the slopes, slopes and plains of the west, to the sea shores. On the northern rivers began in Chili and Quilca —Arequipa—, although more sharply from the current department of Moquegua, finishing in the south, in the Camarones, though quinientistas documents assert that stretched from Camaná up the small river of Pica-Loa. Consequently, enclosed valleys and deserts, apart from the beaches occupied by fishermens or monkeys camanchacas exchanging their products with farmers and ranchers. Among Collisuyo and Lake Puquinacocha (Titicaca) Urcosuyo the field stood. To the east of that palude other subdivision called Umasuyo was. And beyond the Manca named. There were creations of the Incas, but unsaturations made in older ages.